Reactive distillation for the production of cyclohexanol : experiments and simulations - Sun, Dahai (Array, 2021)
Cyclohexanol is an organic chemical intermediate product widely used in chemical industry and commonly produced by cyclohexene hydration. Because of the low mutual solubility of cyclohexene and water, the reaction is limited by chemical equilibrium, which has the disadvantage of low conversion of cyclohexene. In this paper, the hydration reaction of cyclohexene catalysed by A-36 cation exchange resin catalyst was analysed by Aspen Plus V8.6 simulation software in the presence of isophorone as cosolvent. The process model of synthesising cyclohexanol by catalytic distillation was verified by process experiments. The simulation experiments were carried out using the process model, and suitable operating conditions of the catalytic distillation column were obtained. These are: ketene feed ratio 1.5, alkene/water ratio 0.5, distillation stage trays 5, reaction stage trays 12, stripping stage trays 6, cyclohexene feed at the 18th tray, water and isophorone feed at the 5th tray, reflux ratio 3, feed ratio (D/F) 0.25. Under these operating conditions, the conversion of cyclohexene can reach 40.63 %.